Visualizing Web Ontologies with CropCircles - Bijan Parsia; Taowei Wang; Jennifer Golbeck (PROCISWC Workshop on End User Semantic Web Interaction 2005, 2005)
We apply a new visualization for complex heirarchies, CropCircles, to the interactive visualization ofWeb Ontologies and E-Connections of Web Ontologies.